INDIRECT IMMUNOFLUORESCENCE EXPRESSION OF ZO-1 AND PAN-CADHERIN DURING MATURATION OF HEPATOCYTES AND BILIARY NETWORK FORMATION IN MICE (Iraqi Journal of Medical Sciences, 2017)
Background: The tight junctional complexes had been demonstrated in hepatocytes and in both epithelium and endothelium. In multicellular organisms, cell-cell adhesion is critical for development and morphogenesis.Objective: To investigate the spatiotemporal organization of the immunohistochemical markers anti ZO-1 and anti Pan-cadherin during the prenatal development of the mice liver and to correlate the expression of these markers with histogenesis during hepatocyte maturation and biliary network formation.Methods: Forty eight (48) pregnant mice were scarified at subsequent gestational days from day 14 till the first day of postnatal life. Paraffin blocks and sections of the liver extracted from the embryos obtained from these pregnant mice and from neonates at the first postnatal day of life were prepared. The sections were stained using the anti ZO-1 and anti Pan-cadherin immunohistochemical markers.Results: The sequential steps of anti ZO-1 indirect immunofluorescence reactivity in the developing liver tissue showed chronological variability, during days 14, 15, and 16; positive cell surface labeling was weaker adjacent to the blood vessels. The next step includes anti ZO-1 reactivity in late prenatal and postnatal liver tissue showing marked uniform reactivity. The sequential steps were also demonstrated in the anti Pan-cadherin immunohistochemical reactivity. The reactivity of the liver tissue during days 14, 15, and 16 showed disregarded cell surface labeling that increased markedly in later prenatal and postnatal periods.Conclusion: The initial stages in the development include the undifferentiated specification the hepatic lineage characterized by regional establishment of zonula occludens in the developing liver cells and paucity in the development of the zona adherens complexes. The later stages showed histological and functional maturation reflected by anti ZO-1 and anti Pan-cadherin reactivity that represent a requirement for the physiological functions in the entire liver tissue.Keywords: Embryo, mice, Zo-1, Pan-cadherin, immunhistochemistry. Citation: Ali NFM, Mubarak HJ. Indirect immunofluorescence expression of ZO-1 and Pan-cadherin during maturation of hepatocytes and biliary network formation in mice. Iraqi JMS. 2017; Vol. 15(3): 242-249. doi: 10.22578/IJMS.15.3.5
Keywords: Embryo; mice; Zo1; Pancadherin; immunhistochemistry